Pemanfaatan Limbah Oil Sludge Untuk Campuran Beraspal Jenis Laston Pengikat (AC-BC) Dengan Pengujian Marshall) - Trivia Ariska; Gunawan Wibisono; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Petroleum industry has an important role in supplying fuel necessaries. In process to produce pretoleum crude oil into various of petroleum based products also emerged waste products includesolids, liquids and gases. Solid waste products which found from poduction activities of the industry produce called Oil Sludge. Oil sludge is categorized as hazardous and toxic waste (B3) because the characteristic and the concentration can contaminate the environment. This research aims to investigate the potential of oil sludge as a partial replacement of asphalt in Asphalt Concrete -Binder Course (AC-BC). In this study the variation of oil sludge addition was 0%, 4%, 6% and 8% of the weight of asphalt. The addition of oil sludge decreased the optimum asphalt content (OAC) and increased the unit weight of the asphalt concrete mixture. This is caused by the fine grains contained in the oil sludge. Based on the Marshall characteristics test results, the maximum allowable content of oil sludge that could be used was 4% with 6.65% of OAC and 948,03 kg of average stability value which satisfied the specifications of Bina Marga 2010 Revision 3.Keyword : oil sludge, asphalt concrete, AC-BC, marshall, Specification of Bina Marga 2010 Revision 3